1999
DOI: 10.1046/j.1365-2656.1999.00292.x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity patterns in terrestrial dipteran communities

Abstract: Summary 0[ Dipteran communities were studied in _ve terrestrial habitats ðbeech forest "BE#\ oak and hornbeam forest "OH#\ hedgerow "HE#\ meadow "ME#\ alder and willow forest "AW#Ł using emergence traps and diversity patterns of three trophic groups with soil!dwelling larvae "zoophages\ phytosaprophages and surface scrapers# were analysed in detail[ 1[ Across habitats\ sampling e}ort was a poor predictor of species richness\ and species richness increased more steeply with sample size in the zoophages than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The different forms of taxon accumulation curves at the various sites and simulated communities observed in the present study are supported by many previous observations in different organism groups (e.g., Kilburn 1964, Martin 1981, James and Wamer 1982, Karr 1991b, Rosenzweig 1995, Farnsworth and Ellison 1996, Longino and Colwell 1997, Hö vemeyer 1999. This phenomenon has been related to several factors, including habitat diversity and complexity and the size of species pools (e.g., Martin 1981, Angermeier and COMPARISONS OF ECOLOGICAL COMMUNITIES FIG.…”
Section: Effect Of Sample Size On Community Comparisonssupporting
confidence: 91%
See 1 more Smart Citation
“…The different forms of taxon accumulation curves at the various sites and simulated communities observed in the present study are supported by many previous observations in different organism groups (e.g., Kilburn 1964, Martin 1981, James and Wamer 1982, Karr 1991b, Rosenzweig 1995, Farnsworth and Ellison 1996, Longino and Colwell 1997, Hö vemeyer 1999. This phenomenon has been related to several factors, including habitat diversity and complexity and the size of species pools (e.g., Martin 1981, Angermeier and COMPARISONS OF ECOLOGICAL COMMUNITIES FIG.…”
Section: Effect Of Sample Size On Community Comparisonssupporting
confidence: 91%
“…For example, a sample may mean a set of sampling sites and sample size is the number of sampling sites in ecological surveys. A set of collection units from a site or community may be pooled to create a single sample (Colwell and Coddington 1994, Farnsworth and Ellison 1996, Cao et al 1998, Hö vemeyer 1999. Here the use of the terms agrees with statistical definitions.…”
Section: Terminologymentioning
confidence: 99%
“…This in turn determines the diversity of predatory, parasitic and symbiotic species. Diversity of detritivore communities in hedges is also influenced by the variety of leaf litter produced by different species of hedge pants (Hovemeyer, 1999). It is worth noting, however, that not all associations between plant and invertebrate diversity are necessarily directly causal.…”
Section: Botanical Compositionmentioning
confidence: 99%
“…In Australia, only 7,000 of the estimated 30,000 fly species have been documented (Yeates et al, 2003), many of which are found in the dipteran-rich tropical rainforests of north Queensland (Austin et al, 2004). While a number of studies on dipteran communities exist from natural temperate and tropical ecosystems (see Hövenmeyer, 1999;Hughes et al, 2000;Kitching et al, 2004;Wilson et al, 2007;Lambkin et al, 2011), there are almost no formal studies of this group in any countryside landscapes (but see Schweiger et al, 2007;Taillefer and Wheeler, 2012).…”
Section: Introductionmentioning
confidence: 99%